Crohn's disease. (June 2019) - Mak, Wing Yan; Hart, Ailsa L.; Ng, Siew C.
Abstract: Crohn's disease is a chronic inflammatory bowel disease that can affect any part of the gastrointestinal tract from mouth to anus, although the ileum, colon and perineum are most commonly involved. It is characterized by transmural granulomatous inflammation. Crohn's disease is thought to result from a complex interplay of multiple genetic and environmental factors. Alterations in the microbiota signature with reduced microbiota diversity are observed. Diarrhoea, abdominal pain, fatigue, weight loss and fever are hallmarks of Crohn's disease. Clinical features depend on the location and behaviour of disease in the gastrointestinal tract. Extra-gastrointestinal manifestations can involve the joints, skin, eyes and liver. Investigations are directed towards identifying the location, extent and severity/behaviour (inflammatory, stricturing, penetrating) of the disease. The goal of management should be to achieve clinical and endoscopic remission to avoid disease progression and surgical resections. Treatment usually features corticosteroids, immunomodulators (thiopurines, methotrexate), anti-tumour necrosis factor-α therapy or surgery. Newer biological agents included anti-integrin inhibitors and anti-interleukin-12/23 antibody. Patients with poor prognostic features may benefit from early treatment with immunomodulatory drugs and/or biological agents. Therapeutic drug monitoring can help physicians improve and personalize the management of Crohn's disease. Psychological support is also important in managing this chronic condition.